Diadenosine Homodinucleotide Products of ADP-ribosyl Cyclases Behave as Modulators of the Purinergic Receptor P2X7 - Bruzzone, Santina (American Society for Biochemistry and Molecular Biology, 2010)
ADP-ribosyl cyclases from both vertebrates and invertebrates were previously shown to produce two isomers of P1,P2 diadenosine 5′,5′"-P1, P2-diphosphate, P18 and P24, from cyclic ADP-ribose (cADPR) and adenine. P18 and P24 are characterized by an unusual N-glycosidic linkage in one of the adenylic mononucleotides (Basile, G., Taglialatela-Scafati, O., Damonte, G., Armirotti, A., Bruzzone, S., Guida, L., Franco, L., Usai, C., Fattorusso, E., De Flora, A., and Zocchi, E. (2005) Proc. Natl. Acad. Sci. U.S.A. 102, 14509–14514). P24, but not P18, proved to increase the intracellular Ca(2+) concentration ([Ca(2+)](i)) in HeLa cells and to negatively affect mitochondrial function. Here we show that micromolar P24, but not P18, triggers a slow and sustained influx of extracellular Ca(2+) through the opening of the purinergic receptor/channel P2X7. On the other hand, P18 inhibits the Ca(2+) influx induced by 0.6 mm ATP in HEK293 cells stably transfected with P2X7, with an IC(50) of ∼1 μm. Thus, P18 is devoid of intrinsic P2X7 stimulatory activity and behaves as an ATP antagonist. A P2X7-mediated increase of the basal [Ca(2+)](i) has been demonstrated to negatively affect Schwann cell (SC) function in rats with the inherited, peripheral neuropathy Charcot-Marie-Tooth 1A (CMT1A) (Nobbio, L., Sturla, L., Fiorese, F., Usai, C., Basile, G., Moreschi, I., Benvenuto, F., Zocchi, E., De Flora, A., Schenone, A., and Bruzzone S. (2009) J. Biol. Chem. 284, 23146–23158). Preincubation of CMT1A SC with 200 nm P18 restored the basal [Ca(2+)](i) to values similar to those recorded in wild-type SC. These results identify P18 as a new P2X7 antagonist, potentially useful in the treatment of CMT1A.